Application of integrative genomics and systems biology to conventional and in vitro reproductive traits in cattle - Mazzoni, Gianluca; Pedersen, Hanne S.; Junior, Gerson A. de Oliveira; Alexandre, Pamela; Razza, Eduardo M. [UNESP]; Callesen, Henrik; Hyttel, Poul; Nogueira, Marcelo F.G. [UNESP]; Ferraz, Jose Bento S.; Kadarmideen, Haja N. (Colegio Brasileiro de Reproducao Animal - CBRA, 2017)
Assisted reproductive technologies (ARTs) have a strong impact on breeding especially when coupled with genomic selection (GS). The routine implementation of in vitro production (IVP) and GS of embryos before embryo transfer (ET) in breeding companies is not yet possible. Improvement of oocyte donor and embryo recipient quality is needed to make realistic a commercialization of these procedures in the near future. A better understanding of both biological mechanisms and molecular markers associated to IVP-ET related traits is necessary to improve the prediction of donor and recipient cow quality for IVP procedures. The huge amount of data generated from high throughput technologies has a tremendous impact in the search for biomarkers of complex traits. This paper reviews integrative genomics and systems biology approaches as applied to both Bos indicus and Bos taurus cattle reproduction by both conventional and ARTs such as OPU-IVP. The integration of systems biology information across different biological layers generates a complete view of the different molecular networks that control complex traits and can provide a strong contribution to the understanding of traits related to ARTs.
Keywords: Biomarkers; Cattle; Data integration; IVP; Reproduction; Systems biology